Interactional discourse of male and female motivational speech in TED Talks: A corpus-based study (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
TED talks are known for highlighting the speaker’s affective responses to the topic and encouraging the audience to engage along that lead to a great number of interactive functions of discourse markers and features. Thus, the writer is interested in analyzing the interactional discourse markers used in motivational speech in TED talks by comparing the difference between male and female speakers. The data consists of two corpora of TED motivational speeches delivered by male and female speakers with the total of 43160 tokens of female speaker corpus and 51873 tokens of male speaker corpus. The data is analyzed by using Hyland’s stance and engagement features to identify both speakers and audience point of view in the speech. The findings show that female speakers tend to use more of both stance and engagement features than male speakers. It is shown that female speakers tend to be more expressive in composing their speech in order to create an impressive and communicative presentation. Meanwhile, male speakers tend to use more explicit and direct markers in their speech to engage with the audience and focus on delivering the topic and material instead.